1992
DOI: 10.2190/gq2x-t16m-a2wr-eabl
|View full text |Cite
|
Sign up to set email alerts
|

Religion and Drug Use

Abstract: This study is a secondary analysis of data gathered under the sponsorship of the Utah State Division of Alcoholism and Drugs in 1989. The researchers concluded that there is a difference in frequency of alcohol use, source of alcohol, and age of first alcohol use among LDS, Other Religions and No Religion subgroups. There is no significant difference found among the various religious subgroups for age of first marijuana use of quantity of alcohol use. For all religions except Jews, a lower percentage of Utahns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…We confirmed that highly significant husband-wife correlations exist for age, religious attendance and education in agreement with estimates based on other large studies Eaves et al 1990 ;Gilger, 1991). Also, significant associations were observed between psychiatric diagnoses and age, religious attendance and education in both samples, as was expected from previous studies (Hawks & Bahr, 1992 ;Meador et al 1992).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We confirmed that highly significant husband-wife correlations exist for age, religious attendance and education in agreement with estimates based on other large studies Eaves et al 1990 ;Gilger, 1991). Also, significant associations were observed between psychiatric diagnoses and age, religious attendance and education in both samples, as was expected from previous studies (Hawks & Bahr, 1992 ;Meador et al 1992).…”
Section: Discussionsupporting
confidence: 93%
“…Associations between depression or alcoholism and educational level have been reported, usually in the direction of higher rates of psychiatric disorder for lower educational levels. Religious denomination and religiosity are important predictors of problem drinking or patterns of alcohol use (Hawks & Bahr, 1992). Rates of major depression and anxiety also vary among different religious affiliations (Meador et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reflect that religion influences consumer attitude and behavior (Armstrong, 2001;Arnould, Price, & Zikhan, 2004;Burkett, 1980;Cochran & Cohen, 1983;Delener, 1994;Hawks & Bahr, 1992;Matitila, Apostolopoulos, Sonmez, Yu, & Sasidharan, 2001;Pettinger, Holdsworth, & Gerber, 2004). Other studies indicated that religion impacts food purchasing decisions and eating habits in particular (Asp, 1999;Blackwell, Miniard, & Engel, 2001;Mennell, Murcott, & Van Ootterloo, 1992;Mullen, Williams, & Hunt, 2000;Shatenstein & Ghadirian, 1997;Steenkamp, 1993;Steptoe & Pollard, 1995;Swanson, 1996).…”
Section: The Interrelation Between Behavior and Religionmentioning
confidence: 99%
“…Much of this work (54) focuses on the health/lifestyle behaviors of persons within identified religious groups and denominations (e.g. Mormons or Seventh Day Adventists), which may, in turn, result in lower levels of morbidity for various diseases.…”
Section: Health and Lifestyle Behaviors And Health Care Utilizationmentioning
confidence: 99%